Mechanistic insights into sulfadimethoxine degradation via microbially driven Fenton reactions - Zhang, Lan; Wang, Yan; Chen, Xiang; Hang, Xiaoshuai; Liu, Yun (Journal of hazardous materials, 2024)
Biodegradation, while cost-effective, is hindered by the requirement for specialized microorganisms and co-contaminants. Innovative biological technologies like the microbially driven Fenton reaction, hold promise for enhancing degradation efficiency. However, the intricate biochemical processes and essential steps for effective degradation in such systems have remained unclear. In this study, we harnessed the potential of the microbially driven Fenton reaction by employing Shewanella oneidensis MR-1 (MR-1). Our approach showcased remarkable efficacy in degrading a range of contaminants, including sulfadimethoxine (SDM), 4,4'-dibromodiphenyl ether (BDE-15) and atrazine (ATZ). Using SDM as a model contaminant of emergent contaminants (ECs), we unveiled that biodegradation relied on the generation of hydroxyl radicals (•OH) and involvement of oxidoreductases. Transcriptomic analysis shed light on the pivotal components of extracellular electron transfer (EET) during both anaerobic and aerobic periods. The presence of reactive oxidizing species induced cellular damage and impeded DNA repair, thereby affecting the Mtr pathway of EET. Moreover, the formation of vivianite hindered SDM degradation, underscoring the necessity of maintaining iron ions in the solution to ensure sustainable and efficient degradation. Overall, this study offers valuable insights into microbial technique for ECs degradation, providing a comprehensive understanding of degradation mechanisms during aerobic/anaerobic cycling. [Display omitted] •Microbially driven Fenton reaction can effectively degrade SDM, BDE-15, and ATZ.•Biodegradation process relies on hydroxyl radicals and oxidoreductases.•Extracellular electron transfer plays a vital role in anaerobic/aerobic cycles.•The production of vivianite and ROS restrained the biodegradation process.